Uniform consistency of kNN regressors for functional variables - Kudraszow, Nadia Laura (2013)
This paper is devoted to nonparametric analysis of functional data. We give asymptotic results for a kNN generalized regression estimator when the observed variables take values in any abstract space. The main novelty is our uniform consistency result (with rates).